Surgery of Cavernous Hemangioma of the Optic Nerve: Case Report and Review - Ramina, Kristofer; Ebner, Florian H.; Ernemann, Ulrike; Tatagiba, Marcos (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2013)
A case of a cavernous hemangioma of the optic nerve is presented. Cavernous malformations of the cranial nerves are quite rare and have been reported to involve the third nerve, the seventh nerve in the temporal bone, the seventh and the eighth nerves in the internal auditory canal as well as the optic chiasm and optic nerve. We present a case of a patient with a cavernous hemangioma within the right optic nerve, which could be removed by microsurgery with preservation and improvement of vision. Literature on this rare location of cavernoma is reviewed.
Keywords: optic cavernoma; cavernous hemangioma; surgery of optic cavernoma